2001
DOI: 10.1177/152574010102200203
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Practices Related to Augmentative and Alternative Communication

Abstract: Although speech-language pathologists (SLPs) are typically responsible for the treatment of communication problems, the development and implementation of augmentative and alternative communication (AAC) interventions requires the expertise and involvement of additional educational team members (e.g., general and special education teachers, physical therapists, parents). Effective collaboration by these team members is necessary to develop and implement appropriate AAC interventions for students with disabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There is agreement in the literature that AAC is a team approach that includes multiple stakeholders (De Paepe and Wood, 2001; Beukelman et al, 2008; Beukelman and Mirenda, 2005; Ogletree, 2021). Everyone who uses AAC with the individual should be involved in the team (ASHA, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There is agreement in the literature that AAC is a team approach that includes multiple stakeholders (De Paepe and Wood, 2001; Beukelman et al, 2008; Beukelman and Mirenda, 2005; Ogletree, 2021). Everyone who uses AAC with the individual should be involved in the team (ASHA, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…DePaepe and Wood (2001) reviewed AAC training programs in the USA and found that a limited number of pre-service training programs included an emphasis on developing collaborative, problem-solving skills. However, teaching practices in higher education have begun to shift from traditional didactic models to interactive, collaborative, and problem-solving approaches in order to better prepare students to function effectively in collaborative work environments.…”
Section: Introductionmentioning
confidence: 99%
“…In education, spoken language acts as an instrument through which instruction occurs, meanings and connections are formed, and knowledge and skills are transferred and demonstrated (Kathard et al, 2015). School-age children who experience communication difficulties have limited access to this instrument, placing them at risk of potentially adverse effects on their participation, learning and social relationships (DePaepe and Wood, 2001; Thatcher et al, 2008). For children with the most severe speech and language difficulties, their ability to reliably use speech and language to effectively meet their communicative needs across settings with different communication partners is affected (Iacono et al, 2022).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Effective teams engage in frequent, productive and efficient interactions with clearly defined responsibilities and actions, where all members are active and contributive (Hunt et al, 2002; Soto et al, 2001a). Irrespective of the team's composition, size and structure, collaboration between team members is possible (Ogletree, 2021) and deemed essential for AAC service delivery (DePaepe and Wood, 2001; Soto et al, 2001a).…”
Section: Introduction/backgroundmentioning
confidence: 99%